Impact of Pharmacists and Student Pharmacists in Educating and Screening Low-Income Women for Cardiovascular Disease - Natalie A. DiPietro, PharmD, MPH; Kristen Finley Sobota, PharmD, BCPS; Martin R. Giannamore, PharmD, BCPS (University of Minnesota Libraries Publishing, 2012)
Objectives: To evaluate the effectiveness of an educational intervention on knowledge of cardiovascular disease (CVD) and to increase awareness of risk factors among female patients of a community health center with an on-site 340B pharmacy.Methods: The program consisted of a 10-minute educational intervention and brief pre-test, post-test, and participant satisfaction survey. Adult female patients at the clinic for any provider visit or prescription fill were eligible to participate. Participants met individually with a student pharmacist or faculty member and verbally completed the pre-test. The participant received education regarding CVD, risk factors, and symptoms of myocardial infarction and were screened for hypertension and/or hyperlipidemia. The post-test was then verbally administered. Participants answered the satisfaction survey privately. Based on individual needs, educational materials and information on available pharmacy clinical services were provided. The university IRB deemed the study exempt. Results: Eighty-four individuals received educational materials and/or a screening test. Of those, 30 women (mean age 46.9 years) completed the educational intervention. Thirteen (43%) reported smoking; 22 (73%) identified themselves as overweight. Fourteen (47%) indicated a preexisting diagnosis of hypertension. Correct responses for 6 of 8 knowledge-based questions were statistically significantly improved from pre-test to post-test (p<0.05). Twenty-nine patients (97%) rated the program as "useful" or "very useful". Conclusion: CVD is the leading cause of death in U.S. women. Data from this program indicate that through screening and education, pharmacists and student pharmacists can impact female patients' knowledge of CVD risk factors. Continued efforts in this area may help to reduce the public health burden of CVD.